Addressing the impact of environmental noise in public schools in the city of Minas Gerais (Research, Society and Development, 2019)
He noise pollution, followed by water and air pollution, is the environmental problem that affects a greater number of people on the planet, which leads to the search for measures of sound attenuation to avoid the negative effects that may cause in human health. Exposure to noise at levels above the recommended can cause changes in school activities, such as loss of concentration, insomnia, stress, among others. These symptoms may interfere with the ability to perform tasks, thus compromising the school performance. This study aimed to evaluate the acoustic conditions in classrooms of two schools in the city of João Monlevade, Minas Gerais, selected according to the geographic location, being both schools of the state public education network. In addition, the investigation shows the effects of these noises on the day to day of the school community. Acoustic measurements were made inside the classrooms in order to determine the level of noise to which students and teachers are exposed in their daily lives. Subsequently, a questionnaire was applied with the purpose of obtaining information on the knowledge of the theme and on the health of the school community. Finally, a lecture was given to students and teachers of schools, with the aim of bringing information about noise pollution and their impacts on human and environmental health. As for the results, the intensity of the sound pressure level collected in the schools was excessively above the recommended, with perceptible consequences for its users.